2021
DOI: 10.3390/antibiotics10080905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhamnolipids on Growth Performance, Immune Function, and Cecal Microflora in Linnan Yellow Broilers Challenged with Lipopolysaccharides

Abstract: This present study aimed to investigate the effects of rhamnolipids (RLS) on the growth performance, intestinal morphology, immune function, short-chain fatty acid content, and microflora community in broiler chickens challenged with lipopolysaccharides (LPS). A total of 450 broiler chickens were randomly allocated into three groups: basal diet with no supplement (NCO), basal diet with bacitracin (ANT), and basal diet with rhamnolipids (RLS). After 56 d of feeding, 20 healthy broilers were selected from each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…As expected, the present results showed that LPS significantly impaired the growth performance of yellow-feathered broilers by reducing ADG and ADFI and increasing the F/G during days 16–21. Consistently, previous studies have clearly demonstrated that immune stress induced by LPS excitation severely affected ADG and ADFI in broiler chickens; Yang S. et al, 2021 ; Zhang et al, 2021 (Kamboh et al, 2016 ; Li X. et al, 2021 ). Moreover, the induction of immune stress by LPS injection after 14 days significantly affected the growth performance in weaned piglets ( Li Y. S. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As expected, the present results showed that LPS significantly impaired the growth performance of yellow-feathered broilers by reducing ADG and ADFI and increasing the F/G during days 16–21. Consistently, previous studies have clearly demonstrated that immune stress induced by LPS excitation severely affected ADG and ADFI in broiler chickens; Yang S. et al, 2021 ; Zhang et al, 2021 (Kamboh et al, 2016 ; Li X. et al, 2021 ). Moreover, the induction of immune stress by LPS injection after 14 days significantly affected the growth performance in weaned piglets ( Li Y. S. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Increasing evidence also suggested that RES can effectively improve intestinal barrier function ( Wang et al, 2022 ), alleviate the oxidative stress and intestinal inflammation for the enhancement of gut health and performance in piglets ( Cao et al, 2019 ; Qiu et al, 2021 ), ducks ( Yang C. et al, 2021 ), rats ( Wang et al, 2022 ), and mice ( Hao et al, 2022 ) under different experimental models. It has been well demonstrated that LPS could be used to mimick pathogen infection in broilers for studying immune inflammatory responses ( Zhang et al, 2020 , 2021 ; Erinle et al, 2022a ). However, studies on the effects of RES on the growth performance, antioxidant capacity, intestinal health and gut microbiota of yellow-feathered broilers at early stage under LPS challenge conditions remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the growth performance of broilers in an immunosuppressed state is reduced, as evidenced by slower body weight growth and higher FCR ( 46 , 47 ). In this experiment, the FCR increased, and body weight growth slowed down in group M compared to group B.…”
Section: Discussionmentioning
confidence: 99%
“…Broiler chickens are highly susceptible to feed, heat stress, and pathogen infection, resulting in a stress response in the early development of poultry [ 38 , 39 ]. Oxidative stress refers to the disruption of the balance between antioxidants and free radicals that generate various reactive oxygen species (ROS) [ 40 , 41 ]. ROS damages proteins and nucleic acids while producing a large amount of MDA, causing tissue damage, and reducing antioxidant capacity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgA, IgM, and IgG are important immunoglobulins in broilers, which can resist viruses and toxins, protect the immune system, and maintain the health of the body [ 46 , 47 ]. IgG is secreted by plasma cells and has antiviral and antibacterial effects [ 40 ]. IgM has a strong bactericidal effect, activates antibodies, and regulates immune function [ 48 ].…”
Section: Discussionmentioning
confidence: 99%